Risk factors of severe perinatal asphyxia at tertiary hospital - Yayu Dwinita Jasin; Ernawati Darmawan; Martono Tri Utomo (Amaltea Medical Publishing House, 2023)
Background. Perinatal asphyxia is still one of the main causes of neonatal mortality and morbidity, especially in the first week of life in developing countries. In Indonesia, based on data reported by the Directorate of Family Health in 2020, of the 28,158 deaths of infants and toddlers, 72% (20,266 deaths) occurred during the neonatal period. One of the causes of neonatal death is perinatal asphyxia. Objective. To analyze risk factors affecting severe perinatal asphyxia in tertiary hospital. Method. Analytical observational research with case-control design. The data source is secondary data on mothers and babies born at Dr. Soetomo General Hospital from January 1 to December 31, 2021. The inclusion criteria were all neonates with perinatal asphyxia and the exclusion criteria were incomplete data. Results. The prevalence of severe perinatal asphyxia at Dr. Soetomo General Hospital in 2021 is 3.9% (115/2,885). Prematurity was significantly associated with severe perinatal asphyxia (p=0.000). Low birth weight is also significantly related to severe perinatal asphyxia (p=0.000). The most dominant risk factor for severe perinatal asphyxia is prematurity. Extremely preterm have a 232.8 (95% CI: 35.8-2920.3) times higher risk of experiencing perinatal asphyxia compared to very preterm (OR 36.2, 95% CI: 12.4-105.4), moderately preterm (OR 11.6, 95 %CI: 4.1-22.6) and late preterm (OR 3.3, 95%CI: 1.1-9.1). Conclusion. Risk factors for severe perinatal asphyxia are prematurity and low birth weight. Prematurity is the most dominant risk factor for severe perinatal asphyxia in tertiary hospital.